The Paradox of Early Childhood Qur’anic Education: A Critical Analysis of Tahfidz Practices Based on the Tabarok Method and Islamic Psychology Perspective A Case Study at Pondok El-Zahro, Lamongan - Rusiyan; Ishomudin; Khozin (Studia Religia : Jurnal Pemikiran dan Pendidikan Islam, 2026)
This study aims to analyze the paradoxes of Qur’anic education for early childhood through the practice of Qur’an memorization (tahfidz) at El-Zahro Institute, Lamongan, with a particular focus on the implementation of the Tabarok (al-Labudi) method viewed from the perspective of Islamic psychology. The growing trend of tahfidz programs among children reflects the enthusiasm of Muslim communities toward religious education; however, it simultaneously generates pedagogical and psychological challenges. Theoretically, the age of 0–7years is a developmental stage characterized by playfulness and the formation of basic emotions, requiring educational approaches that align with children’s developmental readiness. This study employed a qualitative approach with a case study design. Data were collected through participant observation, in-depth interviews, and documentation involving teachers, parents, and institutional administrators. Data analysis was conducted thematically and reflectively to identify the gap between the ideal concept of the Tabarok method which emphasizes the blessings (tabarok) of early memorization and the psychopedagogical realities of children’s learning experiences. The findings reveal that tahfidz practice at El-Zahro tends to prioritize the quantity of memorization over students’ cognitive, emotional, and spiritual readiness. A paradox emerges when the value of tabarok shifts into academic pressure that neglects children’s psychological well-being. This study recommends a more integrative and compassion-based (rahmah) model of Qur’anic education that balances spiritual values, psychological readiness, and play-based learning approaches as an effective strategy for internalizing Qur’anic values in early childhood.